A brief history of ancient Greek - Colvin, Stephen (Hoboken : Wiley-Blackwell, 2014)
"A Brief History of Ancient Greek accessibly depicts the social history of this ancient language from its Indo-European roots to the present day. Explains key relationships between the language and literature of the Classical period (500 - 300 BC) Provides a social history of the language which transliterates and translates all Greek as appropriate, and is therefore accessible to readers who know little or no Greek Written in the framework of modern sociolinguistic theory, relating the development of Ancient Greek to its social and political context Reflects the latest thinking on subjects such as Koine Greek and the relationship between literary and vernacular Greek "--
The Indo-European Beginnings -- An Aegean Co-Production -- Mycenean Greek -- The Dark Ages -- The Alphabet -- The Greek Dialects -- Homer and the Epic Tradition -- The Language of Greek Poetry -- Bare Words: the Start of a Common Language -- Greek to Romaic and back.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Greek language -- History; Greek language, Hellenistic (300 B.C.-600 A.D.); Greek language -- History; Greek language -- Influence on Latin; Greek language, Hellenistic (300 B.C.-600 A.D.); Latin language -- Foreign elements -- Greek; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Greek language; Greek language, Hellenistic (300 B.C.-600 A.D.); Electronic books; History